PCV2 and PCV3 genotyping in wild boars from Serbia - Nišavić, Jakov (Slovenian veterinary research, 2024)
Porcine circoviruses 2 and 3 (PCV2 and PCV3) are known agents of diseases in domestic pigs and wild boars. PCV2 is an economically important pathogen causing porcine circovirus-associated diseases (PCVAD), while the recently discovered PCV3 is associated with similar disorders. Wild boars can serve as a PCV reservoir for domestic pigs, which is a particular risk for pig farms with low biosecurity. Reports of these infections in Serbia are sporadic, and this study was intended as a follow-up to an earlier study. Our aim was to assess the prevalence and genetic characteristics of PCVs circulating in wild boars in a region in north-eastern Serbia with extensive hunting areas. In our study of 103 samples, 17.48% tested positive for PCV2 and 15.53% for PCV3. The low co-infection rates in 2.94% of the PCR-positive samples, suggests these viruses circulate independently. PCV2 prevalence was lower than in our previous study (40.32% out of 124 samples), but the genetic stability of circulating strains was detected with a clear genotype shift towards PCV2d-2. Moreover, this is the first report of PCV3 occurrence in wild boar in Serbia, and the detected strains were grouped into two genotypes: PCV3-1 and PCV3-3c. The PCV3-1 sequences were clustered with German strains, indicating the prevalence of this genotype in Europe. However, no further geographical correlation could be established, as the PCV3-3c representative was separated within the cluster containing Chinese and Indian strains. Furthermore, there was no correlation between PCV positivity and pathological findings in the sampled animals indicating subclinical infection.
Keywords: genotyping; PCR; PCV2; PCV3; wild boar